O PAPEL DA DIVULGAÇÃO CIENTÍFICA NA FORMAÇÃO DAS CRIANÇAS: A EXPERIÊNCIA DA ESTAÇÃO CIÊNCIA - Tôzo, Carla de Oliveira (2005)
This work analyse the Scientific Spreading realized through by Estação Ciência (USP). The main objectives were: to recoup history and to describe the activities developed for the institution; to identify the used language for the spreading of the scientific concepts; to verify the process of learning of the pupils (3ª and 4ª grades) of a public school during and after the visit; to observe and to analyse how teachers prepare theirs pupils before the visit in the Estação Ciência and to examine the behavior (curiosity/interest) of the public-target in the visit to the Center. The used methodology was Study of Case together with technique of Focal Group. The universe of the research was composed by pupils of the Fundamental Education I (4ª grade), responsible teacher and pedagogic coordinator of the selected school, beyond the director and former-director of the Estação Ciência, as well as the monitors and responsible coordinators by developed activities. The study concluded that is difficulty on the part of the teachers in working scientific concepts, what justifies the importance of the Centers of Sciences as educational support to the schools. However, the Scientific Spreading carried through by Estação Ciência has been little used to advantage for the children, since, the contents is not worked of deepened form in the school. Moreover, children and teachers had felt lack of a bigger pedagogic support of the Center to the School. They had criticized the inadequate use of the language of the monitors and the scarcity of visit time, that to stop for the subjects will be worked of more adequate form.